Keeping up with the Khumalo's: An analysis of the indebted African middle class in South Africa between 2008-2017 - Scott, Thabo (University of Cape Town, 2020)
The demise of apartheid has accelerated the emergence of the African middle class. This group's expenditure pattern has recently received public scrutiny, leading to empirical research on their consumption patterns leaning on the theory of conspicuous consumption. It has also been reported that African middle-class households are becoming more reliant on the use of credit and are becoming overindebted. This study explores the composition of the middle class and the factors that lead African middle-class households to becoming over indebted. The methodology is both quantitative and qualitative. Drawing on the National Income Dynamics Study (NIDS) data, the study examines varying definitions of the middle class in developing country contexts, through comparisons of alternative approaches. This research paper ultimately makes use of the vulnerability approach to define the South African middle class. The empirical results show that the middle class as a whole has grown at a slow rate between 2008 and 2017. However, the African middle class has experienced the most rapid growth, outpacing its white counterpart by a significant margin. The dissertation then uses two waves of (NIDS) data, relating to the periods 2008 and 2017 to present a descriptive analysis of household overindebtedness, which is driven by life-cycle consumption needs. The results show that middle-class households hold a proportionately large amount of debt. Within the middle class, Africans hold the most debt, when compared to other races. To adequately understand the nuances of the indebted African middle class, in-depth interviews were conducted. The results indicate that pertinent issues for this group, such as black tax, contribute to households becoming over-indebted, as this mostly affects the African population group.